Program Pemberdayaan Masyarakat Melalui Inovasi Pengolahan Minyak Jelantah Menjadi Sabun Cuci Sebagai Upaya Mewujudkan Program Desa Hijau di Watukebo, Blimbingsari - Karina Meidayanti; Astri Iga Siska; Nurul Alfiyah (I-Com: Indonesian Community Journal, 2024)
Lack of utilization of household waste, especially used cooking oil (Jelantah) in Watukebo Village, where Jelantah is disposed of carelessly without further processing, causing odors and polluting the environment. Furthermore, it causes odor and environmental pollution. Besides being carcinogenic, used cooking oil, which is dangerous if disposed into the environment, is also included in the category of B3 waste. into the environment. Lack of knowledge about the utilization of Used Cooking Oil by the the Watukebo village community, especially housewives, is one of the obstacles in the efforts to manage household waste that should be utilized in other products of high economic value. One of the ways to handle used cooking oil that is environmentally friendly is by making it laundry soap. To provide appropriate solutions to partners, the cooking oil processing program was carried out in three stages: 1) socializing the making of used cooking oil-based laundry soap to partners, 2) training in making cooking oil-based laundry soap, and 3) managerial training and product business analysis. The results obtained from this activity are liquid laundry soap that is ready to be commercialized and applied to the residents of Bunder Village.